Emily Bronte’s Wuthering Heights: A Study of the Reader’s Response - Yadav, Pravu Ray (Cognition, 2019)
Emily Bronte's Wuthering Heights presents a true love between Catherine and Heathcliff from puritan perception. Their love, however, gets into trouble because of their cultural misunderstanding. Heathcliff is an uncultured character whereas Catherine is a cultured woman. They are spotlessly right in their own place. So, the readers show equal sympathy for both characters because they (Catherine and Heathcliff) are equally innocent in their love affairs. Both are upright in their respective attitude towards each other but both remain unfortunate in society. Their relationship is a subject of deep interest and reflection for the readers.